Levels of hemolytic complement, total C3 and degree of conversion of native C3 in cardiac and indeterminate form of Chagas' disease - Shikanai-Yasuda, M. A.; Souza, Z. T. W.; Yasuda, P. H.; Baueb, S.; Castilho, E. A.; Irulegui, I.; Vaz, C. A. C. (Revista do Instituto de Medicina Tropical de São Paulo, 1984)
The levels of hemolytic complement and total C3 (native C3 plus its degration products) and the degree of conversion of native C3 into its breakdown products were studied in sera from two subgroups of chagasic patients (indeterminate and cardiac forms) and from non chagasic individuals (control subgroup). The levels of total C3 and the degree of conversion of native C3 into its breakdown products were similar in the three subgroups. The levels of hemolytic complement were statistically different among the three subgroups. The lowest average was observed in the subgroup of cardiac patients and the highest average in the control subgroup of non chagasic individuals. The widest variation on levels of hemolytic complement was observed in the subgroup of cardiac patients in which we found the maximum and minimum values among all the subgroups.